Nonalcoholic Steatohepatitis: Involvement of the Telomerase and Proinflammatory Mediators - Serhal, Rim (Biomed Res Int, 2015)
Nonalcoholic steatohepatitis or NASH is an excessive accumulation of fat in hepatocytes accompanied by inflammation and hepatic injury. Proinflammatory molecules such as IL-17, CCL20, S100A8, S100A9, and S100A8/A9 have been shown to be implicated in many types of cancer. Telomerase activity has been found to be associated with chronic inflammation and cancer. NASH can progress to fibrosis then cirrhosis and finally to hepatocellular carcinoma (HCC). Our objective is to try to find a relation between inflammation and the progression of NASH into HCC. We found that there was a significant elevation in the telomerase activity, detected by real-time PCR, between NASH and fibrotic NASH in the liver biopsies of patients. The expression of S100A8, S100A9, S100A8/A9, CCL20, and IL-17, detected by ELISA, is significantly increased in NASH patients with fibrosis in comparison with controls. But, in NASH patients, S100A9, S100A8/A9, and IL-17 only are significantly elevated in comparison with controls. The same, on the mRNA level, expression of IL-17, detected by RT-PCR, is significantly elevated in NASH patients in comparison with controls. Therefore, there is a direct link between the expression of IL-17, CCL20, telomerase, S100A8, and S100A9 in the fibrotic condition and the progression towards cancer.